PUTUSAN PENGADILAN AGAMA TERHADAP ISTERI ATAS MASALAH HARTA YANG DIPERSENGKETAKAN DALAM GUGATAN HARTA BERSAMA DALAM PERKARA PERCERAIAN - Sri Hariati; Musakir Salat (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2022)
The purpose of this study is to find out the decision of the religious court against the wife on the issue of disputed property in a joint property lawsuit in a divorce case at the Religious Court and to analyze the decision of the religious court, a study at the Mataram Religious Court. The problems that will be discussed in this study include how the decision of the religious court against the wife over the disputed property issue in a joint property lawsuit in a divorce case at the Religious Court and what are the obstacles to the court's decision against the wife over the disputed property issue in a joint property lawsuit in a divorce case in Indonesia. Religious courts. The method used is an empirical research method. The results of this study are: Settlement of disputes over the distribution of joint property for Muslims is the authority of the Religious Courts. Legal protection efforts on joint property issues can be taken by placing marital confiscations and joint property claims. The aim is to prevent the misuse of joint property by the husband, so as not to harm the family. The obstacle that often arises in legal protection efforts taken through joint property lawsuits in divorce cases is the limited knowledge of the wife's law, so that in litigation it can affect decisions that are not as expected. In addition, the permitting of the accumulation of joint assets with a divorce lawsuit also creates many problems in the practice of the procedure (procedural law) which are contradictory and take a long time.